Implementation of Scientific Approach in Reducing Student Misconceptions on Energy Matter - Muhammad Amran Shidik; Lidwina Felisima Tae (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
The purpose of this study was to determine the effect of applying scientific approaches to reduce student misconceptions. The subjects of this study were students of Noemuti State High School with a sample size of 58 students obtained through purposive sampling techniques, which were then divided into 2 groups, namely the experimental group and the control group. This research itself is a quasi-experimental research with a Nonequivalent Control Group Design research design. Misconception data was obtained by giving a test in the form of a multiple-choice test of 25 questions with 5 answer choices with the help of CRI. The results showed that the percentage of misconceptions during the pre-test was almost the same between the experimental and control groups, namely 46.05% and 45.25%. Meanwhile, after being given treatment to the experimental group and carrying out a post-test, there was a difference in the percentage of student misconceptions between the experimental and control groups, namely 20.69% for the experimental class and 34.90% for the control group. Furthermore, from the results of data analysis using the t-test, the sig value of the research data was obtained from 0.00 < 0.05. This shows that there is an influence of scientific approaches on reducing student misconceptions where. By using a scientific approach, the reduction of student misconceptions is better than without using a scientific approach.